Different signaling pathways involved in the anti-inflammatory effects of unfractionated heparin on lipopolysaccharide-stimulated human endothelial cells - Xu Li; Lu Li; Yuequan Shi; Sihan Yu; Xiaochun Ma (BMC, 2020)
Abstract Background There is a complex interplay between inflammatory response and coagulation in sepsis. Heparin is used as a recognized anticoagulant and possesses multiple biological properties that possibly affect sepsis. This study aimed to determine the possible signaling pathways involved in the anti-inflammatory effects of unfractionated heparin (UFH) on lipopolysaccharide (LPS)-stimulated human pulmonary microvascular endothelial cells (HPMECs). Methods HPMECs were transfected with siRNA targeting IκB-α. Cells were treated with UFH (0.01 U/ml~ 10 U/ml) 15 min before adding LPS (10 μg/ml). We detected the markers of systemic inflammatory response. Release of interleukin (IL)-6, IL-8 were evaluated at 3 h by ELISA and at 1 h by qRT-PCR. After 1 h, nuclear factor-κB (NF-κB) as well as phosphorylated inhibitor κB-α (IκB-α), signal transducer and activator of transcription-3 (STAT3) and ERK1/2, JNK, p38 mitogen-activated protein kinase (MAPK) expressions were evaluated by Western blot. DNA binding was conducted to further prove the activation of NF-κB pathway. Results In HPMECs, UFH obviously inhibited LPS-stimulated production of IL-6 and IL-8, especially in 10 U/ml. UFH inhibited LPS-induced phosphorylation of IκB-α, ERK1/2, JNK, p38 MAPK and STAT3. UFH also suppressed LPS-stimulated nuclear translocation of NF-κB. Importantly, transfection with siRNA targeting IκB-α induced more obvious inflammatory response. UFH suppressed cytokines production and phosphorylation of different signaling pathways in IκB-α silencing cells. Conclusion These results demonstrate that UFH exerts the anti-inflammatory effects on LPS-stimulated HPMECs by different signaling pathways.